Ensaios em liderança e gestão - Cauduro, Marco Antonio Souza (2018)
The Brazilian public school system offers a rich environment to estimate the effects of leadership on final outcomes, where a lack of market discipline ties the leadership and decision making provided to the student achievement on standardized tests. Principals can influence student achievement in a number of ways, such as hiring teachers, facilitating teaching and learning, managing infrastructure and maintaining student discipline. The first paper measures the effect of individual principals on gains in student math and reading achievement between grades 5 and 9 in Brazil. Using the mobility of principals across schools to identify principal effects, I estimate that a one standard deviation improvement in principal fixed characteristics quality can boost student performance by 0.8 standard deviations in both math and reading. Also, we show that principal tenure does exert an influence on student performance but its effects marginally decrease after seven years of tenure. My results show that principal overall experience does not influence student achievement. The second paper measure the effect of school management practices on the student’s test performance. This thesis draws on unique data collected from survey responses of school principals and teachers to construct a management index that presents a descriptive evidence of management quality adopted by principals of public schools in Brazil. Using a large database of more than 68.000 different schools and a longitudinal panel data from 2007 to 2013, this research identifies a positive and significant relationship of management quality and test performance. The management index captures five different management dimensions: people, governance, leadership, collaborative leadership and processes. This research suggests that the principals could be hired and trained to execute managerial tasks, and the adoption of best practices can affect positively the student’s test-performance.